2014
DOI: 10.1039/c4sc00045e
|View full text |Cite
|
Sign up to set email alerts
|

Functionalised staple linkages for modulating the cellular activity of stapled peptides

Abstract: A divergent synthetic strategy for generating helical p53 peptides bearing functionalised staple linkages, allowing for efficient optimisation of cellular activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
228
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(238 citation statements)
references
References 42 publications
7
228
0
3
Order By: Relevance
“…Double-click reactions involving two side chains with azido functional groups at the i, i + 4 or i + 7 positions and a dialkynyl linker (Fig. 1c) have also been used to enhance helicity in peptides derived from the GCN4 leucine zipper and p53 transactivation domain [51,52]. These reactions allow for wider exploration of chemical space than hydrocarbon staples because different dialkynyl linkers can be installed.…”
Section: Triazole Staplesmentioning
confidence: 97%
See 1 more Smart Citation
“…Double-click reactions involving two side chains with azido functional groups at the i, i + 4 or i + 7 positions and a dialkynyl linker (Fig. 1c) have also been used to enhance helicity in peptides derived from the GCN4 leucine zipper and p53 transactivation domain [51,52]. These reactions allow for wider exploration of chemical space than hydrocarbon staples because different dialkynyl linkers can be installed.…”
Section: Triazole Staplesmentioning
confidence: 97%
“…Limited investigations into the effect of stereochemistry indicate that the (S,R) configuration might be more favourable than (S,S) for the i, i + 4 triazole staple [63], although a more exhaustive study is required to examine and characterise all possible stereochemical combinations. Only the (S,S) configuration has been adopted for the i, i + 7 triazole staple in double-click stapling and the effect of stereochemistry has not been examined [52]. So far, the unnatural residues used to form the triazole staples are monosubstituted, and do not have an a-methyl group.…”
Section: Staple Stereochemistrymentioning
confidence: 99%
“…36,37 The aim of our investigations was to exploit the two-component nature of the double-click reaction by stapling a single peptide with different functionalised dialkynyl linkers (Fig. 13).…”
Section: Functionalised Double-click Linkersmentioning
confidence: 99%
“…Another example includes the design of p53 and structurally related phage display-derived stapled helical peptides having high binding affinity to both MDM2 and MDMX that has been successfully achieved. 42,57,58,65,66,72,79,81,82,87,94,95 In the case of BID BH3 stapled peptides, proof-of-concept studies demonstrating in vivo efficacy in a human leukemia xenograft model (10 mg kg À1 dosing intravenously qd for seven days) were achieved, subsequent to an iterative process to identify a molecule having enhanced proteolytic and serum stability, high binding affinity to anti-apoptotic protein Bcl-2, cell penetration and mitochondrial co-localization, and cytochrome C-driven cellular apoptosis. 43 Recent studies have further shown the successful development of BIM BH3 and BID BH3 stapled peptides which are capable of directly activating the pro-apoptotic protein BAX to affect apoptosis.…”
Section: Intracellular Therapeutic Target Drug Discoverymentioning
confidence: 99%
“…[19][20][21][22][23][24][27][28][29] and 62 for reviews) for the modulation a plethora of intracellular targets (i.e. Bcl2-family, 19,[22][23][24]43,47,48,58,[67][68][69][70][71]76,77,83,92,93,98 p53:MDM2/X, 42,57,65,66,72,79,81,82,87,89,94,95 MAML:Notch, 49 eIF4E, 158 ERa/ERb, 50 IRS1, 84 HIF-1:p300, 56,90 RAS:SOS, 59 Rab-GTPase, 96 b-catenin, 64,78,80 protein kinase-A, 91 RPA, 97 HIV-1 integrase, …”
Section: Stapled Peptide Modulation Of Drug Target Spacementioning
confidence: 99%